3/13 - 5/11 - 1,5 + 10/13 - 6/11 Tham khảo câu trả lời từ Trợ lý ảo Lazi a) To solve this expression, we need to find a common denominator for the fractions. The common denominator for 13 and 11 is 143. 3/13 - 5/11 - 1.5 + 10/13 - 6/11 = (3*11)/(13*11) - (5*13)/(11*13) - (1.5*143)/143 + (10*11)/(13*11) - (6*13)/(11*13) = 33/143 - 65/143 - 214.5/143 + 110/143 - 78/143 = (33 - 65 - 214.5 + 110 - 78)/143 = -214.5/143 = -1.5 b) To solve this expression, we need to simplify the fractions and then perform the division. 25 3/19 : (-5/4) - 5 3/5 = (25*19 + 3)/19 : (-5/4) - (5*5 + 3)/5 = (475 + 3)/19 : (-5/4) - (25 + 3)/5 = 478/19 : (-5/4) - 28/5 = 478/19 * (-4/5) - 28/5 = -1912/95 - 28/5 = (-1912*5 - 28*95)/95*5 = (-9560 - 2660)/475 = -12220/475 c) To solve this equation, we need to find the values of x that make the equation equal to zero. (3/2 - 2x)(5x - 15/4) = 0 Setting each factor equal to zero: 3/2 - 2x = 0 5x - 15/4 = 0 Solving the first equation: 3/2 - 2x = 0 2x = 3/2 x = 3/4 Solving the second equation: 5x - 15/4 = 0 5x = 15/4 x = 3/4 Therefore, the solution to the equation is x = 3/4. d) To solve this equation, we need to find the value of x that satisfies the equation. (x-1)^3 = -1/27 Taking the cube root of both sides: x-1 = -1/3 Adding 1 to both sides: x = -1/3 + 1 x = -1/3 + 3/3 x = 2/3 Therefore, the solution to the equation is x = 2/3.